Factors Influencing Teachers’ Concerns Regarding the Evaluation System of Primary School Curriculum Innovation - Badeni (Language, Literature and Education: Research Updates Vol. 1, 2025)
This study explores the factors influencing teachers’ concerns regarding evaluation systems in primary school curriculum innovation. Understanding these factors is crucial for effective implementation a acceptance of new evaluation methods in educational settings. Evaluation systems play a vital role in assessing student learning and guiding curriculum innovation. They help in identifying strengths and weaknesses, thus ensuring that educational methods remain relevant and effective. The purpose of the study is to describe the teachers’ stage of concern for the evaluation of primary school innovation and factors affecting teachers’ stage of concern. The approach used in this study was a descriptive study. Data related to factors affecting teachers’ stage of concern to the evaluation of primary school curriculum innovation were collected in the form of forum discussion and study of related literature. Data on the teacher’s stage of concern itself to the evaluation system of primary school curriculum innovation were collected, classified, processed and analyzed by using the norms of the group in the calculation of percentile. The result of the study indicates that teachers’ stage of concern for the evaluation of primary school curriculum innovation was low. Several factors contributed to this, including: (a) Lack of understanding among primary school teachers regarding the information received, (b) Absence of examples and evidence demonstrating the benefits of accepted curriculum innovation in school practices, (c) Insufficient training provided by trainers on applying the new curriculum, (d) Complexity in evaluating the curriculum, (e) Continuous changes in the curriculum, (f) Limited teacher involvement in implementing programs and addressing training needs, (g) Inadequate time for teachers to learn, practice, master, and apply curriculum innovation, (h) Teachers’ commitment to implementing curriculum innovation, (i) Principals’ knowledge of educational change, (j) Principals’ role in executing programs, (k) Principals’ moral support and active participation, (l) Collaborative planning between teachers and administrators, (m) Availability of professional development opportunities, (n) Effective feedback mechanisms, (o) Resource availability, and (p) Challenges to teacher engagement. These factors highlight the need for targeted interventions to support teachers in effectively evaluating and implementing curriculum innovation.